Membangun Ekosistem Pendidikan Unggul: Peran Lembaga Sosial Sebagai Pilar Transformasi Pendidikan - Riska; Samsinar Syarifuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Education is the primary foundation of human civilization. However, PISA 2022 data ranked Indonesia 63rd out of 81 countries, indicating that educational challenges cannot be addressed by formal institutions alone. Excellent education cannot be realized through the efforts of individual schools alone, but requires a collaborative and synergistic ecosystem involving various stakeholders. This article seeks to analyze the contribution of social institutions in realizing an excellent, inclusive, and transformative educational ecosystem. The method employed is a literature review through the exploration of academic sources from Google Scholar, ERIC, Scopus, and SINTA. The findings reveal that family, educational, religious, legal, and economic institutions play complementary roles in shaping a quality educational ecosystem. The family functions as the primary socialization agent, schools as structured knowledge transmitters, religious institutions as moral shapers, and economic institutions as determinants of educational access. The synergy among these social institutions serves as a catalyst for inclusive and equitable educational transformation. In conclusion, a strong educational ecosystem can only be realized through integrated collaboration among all social institutions in society.